Impact of bundle implementation on the incidence of peri/intraventricular hemorrhage among preterm infants: a pre-post interventional study - Wallau, Cristiane Akemi Koyama; Costa-Nobre, Daniela Testoni; Leslie, Ana Teresa Figueiredo Stochero; Guinsburg, Ruth (São Paulo Medical Journal, 2021)
BACKGROUND: Peri/intraventricular hemorrhage (PIVH) is a frequent cause of death and morbidity among preterm infants. Few studies have addressed the use of bundles for preventing PIVH. OBJECTIVE: To evaluate the efficacy of a bundle of interventions designed to decrease the incidence of intraventricular hemorrhage at hospital discharge among preterm infants. DESIGN AND SETTING: Pre-post interventional study with retrospective and prospective data collection performed before and after bundle implementation in the neonatal intensive care unit of a university hospital. METHODS: Infants with gestational age < 32 weeks without malformations, who survived > 6 days were included. The bundle consisted of the following actions during the first 72 hours of life: maintenance ofhead in neutral position with the body in supine position, minimal handling, including delay of lumbar puncture until after 72 hours and absence of respiratory therapy maneuvers. Cranial ultrasound as performed on days 3, 7 and 28, or later if needed. The effect of the bundle was analyzed through logistic regression and results were adjusted for confounding variables.RESULTS: 167 infants met the inclusion criteria; 146 (87%) were analyzed. Bundle implementation was associated with decreased chances of PIVH at hospital discharge (odds ratio 0.29; 95% confidence interval 0.13-0.65). Cerebrospinal fluid collection within the first 72 hours increased the odds of PIVH of any grade during the hospital stay fourfold, after adjustment for all variables included in the model. CONCLUSION: Implementation of a bundle of interventions to avoid intraventricular hemorrhage was effective for decreasing the incidence of all grades of PIVH in preterm infants.